Proton Lifetime in Minimal Supersymmetric SU(5) with Gauge Mediation - Jason L. Evans; Yoshihiro Shigekami (European Physical Journal C: Particles and Fields)
Abstract In this paper, we discuss the predicted proton lifetimes in minimal supersymmetric (SUSY) SU(5) grand unified theory (GUT) with gauge mediated supersymmetry breaking (GMSB). We focus on the case of $$5 + \bar{5}$$ 5 + 5 ¯ messengers and determine the low-scale mass spectrum of the scalar particles and gauginos using the renormalization group equations. With the obtained mass spectrum, we calculate the dominant proton decay mode for SUSY SU(5) GUT, $$p → K^+ \bar{ν }$$ p → K + ν ¯ . In our setup, we assume the messenger scale to be $$\mathcal {O}(10^3)$$ O ( 10 3 ) TeV in order to obtain a proper Higgs mass in GMSB scenario. For this messenger scale, we find the proton lifetime is consistent with current experimental limits and can be tested by future proton decay experiments.